Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ijms19030693
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Subtype-Dependent Role of Connexin 43 (GJA1) in Breast Cancer

Abstract: Gap junction transmembrane channels allow the transfer of small molecules between the cytoplasm of adjacent cells. They are formed by proteins named connexins (Cxs) that have long been considered as a tumor suppressor. This widespread view has been challenged by recent studies suggesting that the role of Connexin 43 (Cx43) in cancer is tissue- and stage-specific and can even promote tumor progression. High throughput profiling of invasive breast cancer has allowed for the construction of subtyping schemes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
4
16
0
Order By: Relevance
“…Researchers already confirmed that the connexin gene family played a complicated role in tumorigenesis and progression 21 . Recently researcher found that GJA1 was associated in glioblastoma cancer cells apoptosis and promote the progression and invasion in breast cancer cells 22,23 . Few research about GJA1 was conducted in GCa, one of them suggested that overexpression of GJA1 leads to decreased ability of colony forming and invasive ability in BGC‐823 cells, 24 which was consistent with our research results.…”
Section: Discussionsupporting
confidence: 90%
“…Researchers already confirmed that the connexin gene family played a complicated role in tumorigenesis and progression 21 . Recently researcher found that GJA1 was associated in glioblastoma cancer cells apoptosis and promote the progression and invasion in breast cancer cells 22,23 . Few research about GJA1 was conducted in GCa, one of them suggested that overexpression of GJA1 leads to decreased ability of colony forming and invasive ability in BGC‐823 cells, 24 which was consistent with our research results.…”
Section: Discussionsupporting
confidence: 90%
“…There was no differential Cx43 expression between the different subtypes and a correlation between Cx43 and ER/PR/erbB2 could not be established in the examined tissues [28]. Consistently, Busby et al, 2018 report that Cx43 expression depends greatly on intrinsic subtype [52]. Most importantly, Arora et al, 2018 report that decreased GJA1 expression leads to worse survival outcomes in patients, in several cancers including breast cancer [53], and another recent study reported Cx43 as an independent predictor of breast cancer patient prognosis and outcome [54].…”
Section: Discussionmentioning
confidence: 94%
“…GlialCAM expression is also sufficient for reducing Notch-mediated invasion and migration in prostate cancer cells [ 282 ]. Lastly, GlialCAM stabilises connexin-43 at cell-cell gap junctions [ 287 ], connexin-43 being a potential tumour suppressor itself [ 288 , 289 ]. In summary, GlialCAM has a strong anti-proliferative influence when expressed in cancer cells, which could underpin its role as a tumour suppressor.…”
Section: − Channelsmentioning
confidence: 99%